1997
DOI: 10.1606/1044-3894.738
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Domestic Violence on Children

Abstract: The author examines the negative behaviors of children in milieus in which sheltered women report and do not report the occurrence of child abuse. The sample of women was randomly selected from those sheltered in a midwestern regional family-violence center at some point during a 22-month period. Data on children's negative behaviors were collected from women ex post facto by examining the intake forms they completed with shelter workers. The results of the study suggest that social work practitioners take a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
3
16
0
1
Order By: Relevance
“…Earlier research shows that public health nurses have difficulty identifying abuse (Yam, 1995; Dickson & Tutty, 1996) and that they do not use effective tools for identification (Chalmers, 1994; Appleton, 1996). Previous studies also show that abuse is manifested in the child's appearance and behavior (Markward, 1997). Family functioning and family behaviors are also associated with the prevalence of abuse (Gaudin et al., 1996).…”
Section: Resultsmentioning
confidence: 95%
“…Earlier research shows that public health nurses have difficulty identifying abuse (Yam, 1995; Dickson & Tutty, 1996) and that they do not use effective tools for identification (Chalmers, 1994; Appleton, 1996). Previous studies also show that abuse is manifested in the child's appearance and behavior (Markward, 1997). Family functioning and family behaviors are also associated with the prevalence of abuse (Gaudin et al., 1996).…”
Section: Resultsmentioning
confidence: 95%
“…Of those reporting specificity effects, two reported specificity for externalizing outcomes (DePaul & Arruabarrena, 1995; Williamson et al, 1991), and one reported specificity for internalizing outcomes (Prino & Peyrot, 1994). The two Outcome specific studies to examine both internalizing and externalizing outcomes failed to find evidence of specificity (Famularo, Kinscherff, & Fenton, 1992; Markward, 1997).…”
Section: Abusementioning
confidence: 99%
“…Research has addressed the causes and identification of risks of child maltreatment (20–25), sexual abuse and incest (26, 27), consequences of maltreatment (28, 29) and psychological maltreatment (30). Family dynamics in child maltreating families has also been addressed (22, 25, 31).…”
Section: Introductionmentioning
confidence: 99%
“…Child maltreating families have multiple problems, and family functioning in these families has been described as more chaotic and unorganized than in other families with children (25, 31). Consequences of maltreatment for the child include problems at school, emotional problems and depression (28, 29, 32).…”
Section: Introductionmentioning
confidence: 99%